Motivational pathways from antecedents of alcohol use to consequences: a structural model of using alcohol to cope with negative affect. (3rd July 2016) - Blevins, Claire E.; Abrantes, Ana M.; Stephens, Robert S.
ABSTRACT: Background : Drinking among college-aged individuals can be problematic. The motivational model of use, which examines various cognitive factors, personal characteristics, and environmental factors, can provide a greater understanding of what contributes toward the decision to drink in these young adults. Objectives : The current study evaluates proposed paths from risk factors for alcohol use, motives for drinking, and subsequent outcomes of alcohol use, drawing from seminal research on the motivational model and drinking motives. Methods : This model was tested in a sample of 303 undergraduate drinkers (77.9% female, mean age = 19.8 years), and evaluated the potential impact of gender and pattern of use. Results : Results indicate that expectancies, maladaptive coping, and negative affect personality styles are associated with coping motives for drinking, and that coping motives are significantly related to problems associated with use. These results are similar for males and females, and among heavy and lighter drinkers. Conclusion : Findings support the role of the coping motive in problematic outcomes associated with drinking and suggest that expectancies, negative affect personality styles, maladaptive coping, and drinking motives are potential targets of prevention and intervention.